Thomas & friends all engines go. The mystery of Lookout Mountain [videorecording (DVD)] - Allcroft, Britt; Suvalle, Rick, 1972- (NCircle Entertainment, 2023)
When cars go missing in the Mines, Thomas and Percy think they have a perfect adventure for the Biggest Adventure Club. Their search takes them under waterfalls, into unknown tunnels, new Crystal Caverns and face to face with a mythical Mine Monster!